First Total Synthesis of (3R,4S)-4-Hydroxylasiodiplodin: A Facile and Stereoselective Approach - Bujaranipalli, Sheshurao; Eppa, Gyan Chander; Das, Saibal (Synlett, 2013)
A first total synthesis of (3R,4S)-4-hydroxylasiodiplodin is described starting from methyl acetoacetate and a commonly available carbohydrate, d-mannitol, which is regularly used in organic synthesis. The facile and stereoselective approach involves the Barbier allylation and a ring-closing metathesis as key steps.
Keywords: Hydroxylasiodiplodin; Barbier allylation; metathesis; carbohydrate; total synthesis; natural product